LATERAL MEDULLER SENDROMUN BİR BULGUSU OLARAK HIÇKIRIK VE TEDAVİSİ: DÖRT OLGU SUNUMU - PELİN, Zerrin and BOZLUOLCAY, Melda and ERKOL, Gökhan and BUGAY, Gülcan and Denktaş, Hayrünnisa (Cerrahpaşa Medical Journal, 2014)
Background.- Hiccup is a reflex originated activity that is characterized by an intermittent contraction of diaphragm followed by glottic closure. Among the various systemic causes including gastrointestinal system and cardiovascular system disorders, this activity is also seen as a symptom of lateral medullary syndrome. If hiccup becomes a sustained activity, beginning to treatment is unevitable. In this report, chronic hiccup as a sign of lateral medullary syndrome was evaluated in 4 cases and the alternatives of treatment against hiccup was debated. Observation.- 4 cases with an acute onset neurological symptoms together with hiccups were diagnosed as lateral medullary syndrome based on their neurological examinations and cranial imagings. Hiccup is evaluated as a symptom of lateral medullary syndrome and treated with different medications. Chlorpromazine, valproic acid and baclofen constituted treatment alternatives against hiccup in different dosages and combinations. The full recovery from hiccups was observed in all patients.